The economic crisis as depicted in film : a Singaporean context. - Lim, Pei Yee. (2008)
This paper tries to examine how three Singaporean films - Money No Enough(1998), Lucky Number(1999) and Where Got Problem(1999)- portray the 1997 Asian economic crisis.